Analysis Of The Implementation Of The Non-Conviction-Based Concept In The Practice Of Asset Recovery Of Money Laundering Criminal Act In Indonesia From The Perspective Of Presumption Of Innocence - Ana Fauzia; Fathul Hamdani (Muhammadiyah University Press, 2021)
Purpose: This research aims to analyze the discourse on applying the non-conviction-based concept in the practice of restoring money laundering assets in Indonesia from the perspective of the presumption of innocence. Methodology: In this research, the method used was normative juridical using statutory, conceptual, and historical approaches. Results: The research results present a concept of the importance of the presumption of innocence and protection of the suspect's property before they are stated or convicted in court. Given the non-conviction-based concept in the assets recovery practice of money laundering crime, it is a mechanism for seizing state assets that criminals have taken, and it is possible to confiscate them again, even though the initial criminal act is not yet known for certain guilt so that it has the potential to castrate the suspect's human rights. Applications of this study: This article explains the importance of safeguarding the presumption of innocence and protecting the property rights of suspects. It is crucial to be used as a reference considering that the criminal procedural law system in effect in Indonesia is also inadequate to apply this concept. Thus, if this concept will be applied in the future, this study can be a reference in terms of drafting related regulations to safeguard against the presumption of innocence and the rights of suspects. Novelty/Originality of this study: The non-conviction-based concept in the asset recovery practice of money laundering crime is new. Therefore, the research presents to analyze whether the concept is under the existing legal system in Indonesia.